DESIGNING AN INTEGRATED SKILLS TEACHING STRATEGY USING PROJECT BASED-LEARNING - Rita, Digna; ., Ikhsanudin; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The main aim of this study is to design the appropriate integrated skills teaching strategies using project-based learning for grade XI students. The research was conducted at SMA Negeri 1 Bengkayang involving XI grade students of science class and two English teachers. This research followed ADDIE’s procedure. The researcher conducted observation, interview and administered questionnaires for the data collecting. In addition, the researcher obtained validation from the experts to improve the quality of teaching strategy designed in this study. The result of this study was A Gallery Exhibition Project that can be used as supplementary teaching strategy. It comprised of three parts i.e., Pre-project activities (planning the project), whilst-project activities (conducting the project outside the classroom/preparing the project) and post-project activities (presenting the project). Keywords: Design; Integrated skills; Project-based. Abstrak: Tujuan utama penelitian ini bertujuan: untuk merancang strategi pembelajaran terpadu berbasis proyek yang dilaksanakan pada siswa kelas XI. Penelitian ini dilaksanakan di SMA Negeri 1 Bengkayang melibatkan para siswa kelas XI MIPA dan dua orang guru bahasa Inggris. Penelitian ini menggunakan prosedur ADDIE. Peneliti melakukan pengamatan (observasi), melakukan wawancara dan kuisioner. Selain itu, peneliti menvalidasi produk yang dilakukan oleh para ahli untuk meningkatkan kualitas dari strategi pengajaran dalam penelitian ini. Hasil utama penelitian ini adalah A Gallery Exhibition Project yang dapat digunakan sebagai tambahan program pengajaran. Strategi pengajaran ini terdiri dari tiga bagian yaitu pre-project (perencanaan kegiatan proyek ), whilst-project (kegiatan pelaksanaan proyek di luar kelas/mempersiapkan proyek) dan post-project (mempresentasikan kegiatan proyek). Kata kunci : Desain; Keterampilan terpadu; Berbasis-proyek.